A review of North American Elonus species, with description of E. gruberi n. sp. (Coleoptera: Tenebrionoidea: Aderidae) - Gompel, Nicolas (Zootaxa, 2017)
This work provides a taxonomic survey of the North American species of the genus Elonus Casey, 1895 (Coleoptera: Tenebrionoidea: Aderidae). It includes the description of a new species, Elonus gruberi n. sp. from the United States, related to E. hesperus Werner, 1990 and to E. basalis (LeConte, 1855). A review and key to the North American species is provided.